VERBAL FLUENCY SEBAGAI DOMAIN KOGNITIF YANG PALING MEMENGARUHI AKTIVITAS FUNGSIONAL LANSIA DI PULAU JAWA - Pricilya H. Wangi; Yvonne Suzy Handajani; Yuda Turana (PERDOSNI, 2021)
Introduction: The prevalence of cognitive impairment and functional disability increases with age. Decreases in cognitive subdomains increase the risk of functional disability in the elderly. Aim: Obtain an overview of the ability of the elderly in carrying out functional activities as well as risk factors, especially cognitive disorders in the elderly community on the island of Java. Method: A cross-sectional study using secondary data from the 2014-2015 Indonesian Family Live Survey (IFLS-5) was conducted on respondents aged 60 years or older. Impaired cognitive function was assessed using the Telephone Survey of Cognitive Status (TICS) method. There are several cognitive domains in the TICS with a total score of 0-34, with the possibility of experiencing global cognitive impairment if the score is ≤13. Verbal fluency is said to be impaired with a value of <16. Elderly independence was assessed using the Instrumental Activity of Daily Living (IADL). Result: Obtained 1688 respondents, mostly aged 60-74 years (88.7%), women (54.3%), with less than nine years of education (72.8%), and living in urban areas (58.4%). A total of 26.7% of respondents experienced global cognitive impairment, 73.6% of respondents with impaired verbal fluency, and 28.6% needed assistance doing IADL. The analysis result shows a relationship between several domains of cognitive function and IADL in the elderly on the island of Java. Discussion: Based on multivariate analysis, the most influencing factor for IADL was age, while the cognitive domain that most influenced IADL was verbal fluency. Respondents over 75 years old and impaired verbal fluency were 2,2 and 1,7 times, respectively, at greater risk of developing IADL dependence. Keywords: Cognitive, elderly, instrumental activity of daily living, verbal fluency.